Clinical and functional eye condition changes in the dry form of age macular degeneration depending on the AREDS stage - D. A. Teuvazhukova; L. L. Arutyunyan; T. G. Tlupova (Российский офтальмологический журнал)
Purpose: to assess the functional state of the eyes in age-related macular degeneration depending on the AREDS classification stage.Material and methods. A clinical study of 60 patients (120 eyes) with the dry AMD form, aged 55.1 ± 4.2 years, involved 30 patients (60 eyes) aged 52.7 ± 3.9 years with AREDS 2 category (initial AMD stage, group1) and 30 patients (60 eyes) aged 57.9 ± 7.8 years with AREDS 3 category (intermediate AMD stage, group 2). The complex research involved visual acuity measurement, including the assessment of near vision in various illumination conditions according to the authors’ methodology, fluorescein angiography, refractometry, tonometry, optical coherence tomography (OCT), ultrasound duplex scanning of the eye; and an immunological study aimed at determining interleukins and interferons in blood serum.Results. Visual acuity was found to depend on test illumination in healthy subjects and to substantially drop at all illumination levels in AMD, especially in the 3rd stage. With the development of AMD, the activity of the immune response was recorded.The patients of groups 1 and 2 showed an increase in the inflammatory response and a depression of the anti-inflammatory response. In group 1, an increase was recorded in IL-I by 23.5% (p < 0.05), in IL5 by 25.4% (p < 0.05), and in IL8 by 19.9% (p < 0.05). In group 2, the value of these parameters exceeded the norm by 32.1, 39.5 and 25.4% (p < 0.05), respectively. The parameters of anti-inflammatory immunity (IL10 and TGF l) were lower than the reference level by 18.3 and 24.6% (p < 0.05) of patients of group 1 and by 24.3 and 30.75 (p < 0.05) of group 2. It was established that the degree of imbalance of the immune system is associated with the stage of AREDS. In group 2 patients with AREDS 3, the content of pro-inflammatory interleukins exceeded those of group 1: IL-I by 12.5% (p < 0.05), IL5 by 11.9% (p < 0.05), IL8 by 11, 2% (p < 0.05). IL10 and TGF l in group 2 were lower than in group 1 by 10.2 and 11.8% (p < 0.05).Conclusion. Near visual acuity measurement depending on test illumination may be used as a sensitive diagnostic test in AMD in patients. At an early stage of AMD development, a disorder in the immune defense is observed, taking the form of activation of the pro-inflammatory spectrum and depression of the anti-inflammatory component, as well as microcirculatory changes Homeostatic changes of the eye appear at an early stage of the disease and are progressing as the clinical picture is deteriorating. The changes are the greatest at patients with stage 3 of AREDS.